System pomiaru ryzyka rynkowego w długim horyzoncie czasowym EAR - Karwański, Marek; Jałowiecki, Piotr; Orłowski, Arkadiusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
Risk assessment methods are one of the most significant components of risk management systems used in financial institutions. Risk factors are assessed with using of VaR (Value at Risk) methodology based on stochastic models. These methods are used only for short-term wallets. More significant there are EaR (Earning at Risk) models enabling long-term analysis of traditional wallets. These models consists of simulation models of market data and evolution models of wallet structure and wallet volume. In this paper the first part of EaR methodology – long-term simulation models of risk factors is studied. Using of EaR methodology is presented for real risk management system from one of the commercial banks